MECHANICAL CHARACTERISTICS AND STRUCTURE OF MOLYBDENUM ALLOY CМ-10 IN TEMPERATURE RANGE OF 298 – 1473 K - Маrinchenko, G.Е. (Proceedings of National Aviation University (archive), 2005)
The influence of a test temperature on the mechanical characteristics of the molybdenum alloy samples of CМ-10 is considered. It is shown, that deformed by rolling molybdenum alloy has anisotropy of mechanical characteristics. The maximum value of strength properties is reached on transversal samples. The maximum value of relative elongation corresponds to longitudinal samples. Strength properties of samples are monotonically reduced while test temperature increasing. Plastic properties in the temperatures range of 273 – 1273 K are reduced, and then they sharply increase reaching 25 – 35 % at test temperature of 1473 К.